Gambaran Pengetahuan Ibu Tentang Gizi Seimbang Pada Anak Balita Usia 12-59 Bulan Di Desa Ped, Kecamatan Nusa Penida - Rismayanti, Ni Putu Winda; Astiti, Ni Komang Erni; Suindri, Ni Nyoman; Erawati, Ni Luh Putu Sri; Budiani, Ni Nyoman (Innovative: Journal Of Social Science Research, 2025)
The stunting case in Ped Village is relatively high with a percentage of 6.89% so that mothers' knowledge needs to be improved. The purpose of this study was to determine the level of mothers' knowledge about balanced nutrition in toddlers aged 12-59 months in Ped Village, Nusa Penida District. This type of research is descriptive quantitative with a cross-sectional approach. The implementation of the study in Ped Village during the integrated health post (Posyandu) activities on May 7-13, 2025, using the proportionate cluster random sampling technique. The research sample was 85 mothers of toddlers who participated in the Posyandu activities in Ped Village by distributing a 30-question questionnaire. Data analysis used univariate in the form of percentages. The results showed that mothers' knowledge about balanced nutrition in Ped Village was in the sufficient category (60%), while knowledge based on indicators: the definition of balanced nutrition was in the good category (45.9%), the benefits of balanced nutrition were in the good category (58.8%), the principles were in the good category (43.5%), the grouping of balanced nutrition was in the sufficient category (42.4%), and the nutritional adequacy rate was in the good category (47.1%). Mothers' knowledge in Ped Village was classified as quite good.